THE IMPORTANCE OF THE VALUATION OF WATER QUALITY IN IRRIGATION PROJECTS - PATERNIANI, JOSÉ EUCLIDES STIPP; DA SILVA, MARCELO JACOMINI MOREIRA; PIRES RIBEIRO, TÚLIO ASSUNÇÃO; AIROLDI, ROGÉRIO PEREIRA DA SILVA (Revista Brasileira de Engenharia de Biossistemas, 2008)
Theobjective of this study was investigate the influence of water quality in the water blade appliedby irrigation systems placed in citrus culture at São Paulo State. The application happened in fivecitrus production farms, where dripping irrigation systems are used. These systems are made of81 filtering heads that worked with disc filters of 120 mesh. Water samples were collected toanalyze the suspended solids concentration, the turbidity and the apparent color and to classifythem as the drippers clogging risk. Assays to determinate the water uniformity distribution index bythe emitters. The results showed that even using filtering systems in the heads, a lot of drippinglines had decurrently problems because of emittersÂ' clogging. This work allows to conclude that amore detailed knowledge of water quality can contribute to choose more efficient adjusted filteringsystems, decreasing the problems that con appear with this kind of irrigation.